2019
DOI: 10.1111/eea.12828
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition preferences in Grapholita molesta: the relative importance of visual and olfactory cues

Abstract: The oriental fruit moth, Grapholita molesta (Busck) (Lepidoptera: Tortricidae), is a major pest of fruit trees worldwide. Females oviposit on the young leaves of peach [Prunus persica (L.) Batsch (Rosaceae)] shoots at twilight, when light intensity changes markedly. Previous researches have shown that the oviposition response of this moth is guided particularly by visual and olfactory cues from host plants. However, the relative importance of visual and olfactory cues in their oviposition preference is largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The selection and location of host plants are crucial for the survival and reproduction of herbivorous insects, which can distinguish nutritional and toxic compounds through their olfactory and gustatory systems [36][37][38]. Adults can detect and distinguish volatile substances from specific plants through VOCs [39][40][41][42], thus helping them search for host plants for oviposition or feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The selection and location of host plants are crucial for the survival and reproduction of herbivorous insects, which can distinguish nutritional and toxic compounds through their olfactory and gustatory systems [36][37][38]. Adults can detect and distinguish volatile substances from specific plants through VOCs [39][40][41][42], thus helping them search for host plants for oviposition or feeding.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, we presented peach Prunus persica Batsch shoots, which are highly attractive to G. molesta females for oviposition (Yang et al, 2019), to test light vs. dark preference in the presence of host odor. Top peach shoots (cv.…”
Section: Methodsmentioning
confidence: 99%
“…Top peach shoots (cv. Shenzhou Honey Peach) with 5 ± 1 leaves that served as the odor stimuli were placed individually into plastic cups containing a block of ‘Oasis’ floral foam to maintain shoot freshness (Yang et al, 2019). Plastic cups were pierced with 30 holes (1.5 mm diameter) in their sides, thereby allowing odors to escape.…”
Section: Methodsmentioning
confidence: 99%
“…Selecting and locating host plants are crucial for the survival and reproduction of phytophagous insects. It is widely believed that olfaction plays predominant roles in this process. Adult females can detect and discriminate volatile semiochemicals from particular plants in a species-specific manner or via specific ratios of ubiquitous compounds and unitize them to select hosts for oviposition or feeding. Plant semiochemicals mediating host selection of several phytophagous insects among crops or varieties with different resistances have been identified. , It was reported that two sesquiterpene volatile compounds (zingiberence and curcumene), which are present in the wild tomato resistant to the tobacco whitefly Bemisia tabaci, but absent in susceptible cultivated tomato, are strongly repellent to B.…”
Section: Introductionmentioning
confidence: 99%